"...lautloses irren, ways of worldmaking, too..." - Postbahnhof, Berlin (Berlin : Postbahnhof am Ostbahnhof Berlin, 2003)
Antille, Emmanuelle ; Bauer, Marc ; Brethouwer, Harmen ; van Brummelen, Lonnie ; Büchel, Christoph ; CineNomad ; Claerbout, David ; collectif_fact ; Diller & Scofidio ; Jodi ; Langelaar, Marije ; MacDonald, Euan ; Mik, Aernout ; Moulin, Nicolas ; Nashat, Shahryar ; Netzhammer, Yves ; Op de Beeck, Hans ; Otto, Catrin ; Perlman, Hirsch ; Rist, Pipilotti ; Rosier, Mathilde ; Sebestyén, Nada ; Smith, Gregg ; Speakman, William ; Tasset, Tony ; Wedemeyer, Clemens von ; Weirich, Susanne
Exhibition in Postbahnhof in Berlin, 29.11.2003 - 02.02.2004
Duits
boek